Plastic Behaviour of Fibre-Reinforced Composites and Fracture Effects - Herrmann, K.; Mihovsky, I.M. (Engineering Transactions, 1983)
The work deals with the problem of longitudinal extension of a unidirectionally reinforced brittle fibres-ductile matrix composite. A model of the plastic deformation process is proposed with regard to a unit cell of the composite. The model accounts in an essential way for the matrix ductility and reveals the nature of the possible mechanisms of failure of the fibre-matrix interface. The model implies a relatively simple general scheme of analysis of the entire problem including, in particular, the determination of the current plastic zone size, the stress-strain curve for the considered composite as well as the important measure of a limiting elastic response of the matrix phase. The detailed solution of the problem associated with the proposed model is shown to require simple numerical calculations. However, certain important results are obtained in a closed form.